2022
DOI: 10.1111/cen.14704
|View full text |Cite
|
Sign up to set email alerts
|

Treatments targeting neuroendocrine dysfunction in polycystic ovary syndrome (PCOS)

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age and is the leading cause of anovulatory subfertility.Increased gonadotrophin releasing hormone (GnRH) pulsatility in the hypothalamus results in preferential luteinizing hormone (LH) secretion from the pituitary gland, leading to ovarian hyperandrogenism and oligo/anovulation.The resultant hyperandrogenism reduces negative feedback from sex steroids such as oestradiol and progesterone to the hypothalamus, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 79 publications
1
28
0
1
Order By: Relevance
“…Intrinsic alterations in ovarian function, characterized by hyperandrogenemia and oligo/anovulation, are considered the direct culprits of PCOS (2). Growing insights into the neuroendocrine system underpinning the heightened gonadotrophin-releasing hormone (GnRH) pulsatility observed in PCOS have shed light on the causes or underlying biological alterations (3). Increased GnRH pulsatility promotes the secretion of luteinizing hormone (LH), which in turn stimulates ovarian androgen secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic alterations in ovarian function, characterized by hyperandrogenemia and oligo/anovulation, are considered the direct culprits of PCOS (2). Growing insights into the neuroendocrine system underpinning the heightened gonadotrophin-releasing hormone (GnRH) pulsatility observed in PCOS have shed light on the causes or underlying biological alterations (3). Increased GnRH pulsatility promotes the secretion of luteinizing hormone (LH), which in turn stimulates ovarian androgen secretion.…”
Section: Introductionmentioning
confidence: 99%
“…[25,26] NKB, a member of the tachykinin family of peptides, is encoded by TAC3 genes in humans and preferentially binds to NK3R. [27][28][29][30][31] Evidence suggests that NKB/NK3R signaling pathways play a pivotal role in central neuroendocrine pathways in human reproduction. [15,[32][33][34] Additionally, it has been found that kisspeptin, a neuropeptide that regulates the hypothalamic-pituitary-gonadal axis, works in concert with NKB in modulating reproductive functions.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the most common causes of infertility in women of childbearing age. It is usually associated with reproductive complications (irregular menstruation, ovulation dysfunction, and pregnancy complications), metabolic disorders (type 2 diabetes and cardiovascular disease), and even psychological risk factors [1][2][3][4]. Depending on the population investigated and the diagnostic criteria used, the prevalence of PCOS ranges from 6% to 15% and approximately 75% of women with PCOS su er from infertility due to ovulation disorders, which makes infertility an urgent problem for PCOS patients [5][6][7].…”
Section: Introductionmentioning
confidence: 99%